Implementasi Kebun Sekolah dalam Mengembangkan Literasi Lingkungan Siswa Sekolah Dasar - Edi Gunawan; Renan Subantoro (Nur Science Institute, 2025)
Background: This study describes the implementation of a school garden and changes in students’ environmental literacy indicators at SDN Ngaliyan 1 Semarang. Method: A descriptive qualitative case-study design was employed. Data were collected from May to July 2025 through observations, interviews, response questionnaires, and documentation. The participants included the principal, [insert number] teachers, and [insert number] students in grade [insert grade]. The implementation involved needs assessment, planning, socialization and training, garden development, garden-based learning, and evaluation. Data were analyzed through data reduction, data display, and conclusion drawing, supported by source and technique triangulation. Result: The findings show that an underused school area was transformed into an outdoor learning environment containing planting beds, vegetables, medicinal plants, plant labels, gardening tools, and a composting area. The comparison of initial and final observations indicated category changes in five indicators: understanding the role of plants, maintaining environmental cleanliness, caring for plants, sorting waste, and collaboration. Teachers also began to use the garden as a contextual learning resource. Implication: The findings suggest that school gardens can function as living laboratories for environmental literacy